- Implementasi Alih Media Koleksi Perpustakaan Sekolah Mekar Arum ke INLISLite untuk Meningkatkan Akses Informasi: - - Lutfia Rahma; Mikhayla Najma Hilmansyah; Dzhia Ledy Ulhaq; Heri Setiawan (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2026)
This research focuses on the implementation of collection media conversion into the INLISLite digital system as part of service development efforts at Mekar Arum School Library. The purpose of this study is to describe the process of implementing collection media conversion and to examine its implementation in supporting improved access to information for library users. This research employs a qualitative approach with a descriptive design, as it aims to understand the processes and dynamics involved in the implementation of media conversion based on real conditions in the field. Research participants were selected purposively and consisted of librarians and intern students who were directly involved in digitalization activities and the use of the INLISLite system. Data collection techniques included observation of library management activities, semi-structured interviews to explore stages, constraints, and the roles of involved parties, as well as documentation in the form of relevant library records and archives. Data analysis was conducted continuously through data reduction, data display, and conclusion drawing in order to obtain a systematic overview of the collection media conversion implementation. This study is expected to provide insights into collection media conversion practices in school libraries and serve as a reference for the development of digital-based library services, particularly in the utilization of library automation systems to support access to information